Plasticity responses of two sympodial bamboo species to nitrogen levels - LI Wei-cheng; WANG Shu-guang; WU Zhi-zhuang; ZHOU Yan; WANG Shu-dong; ZHONG Zhe-ke (浙江大学学报. 农业与生命科学版)
Bamboo has very wide applications such as construction materials, fibre production, biological energy, food and traditional Chinese medicines, etc. Moreover, the area of bamboo forest will increase in future as a result of bamboo industry's development into a pillar industry in rural areas of south China. The limitation of nitrogen supplements in plant growth and biomass is more sensitive than other nutrition elements. So addition of different nitrogen fertilizers will affect the growth procession. Although there are numerous studies focusing on monopodial bamboo species, these types of key researches are missing in sympodial bamboo research, which is negative to the bamboo industry.Investigating the plasticity and physioecology of sympodial bamboo is helpful to comprehend its adaptability under different cultivation and afforestation conditions. In order to understand the relationship between plasticity of sympodial bamboo and soil nitrogen input under the semi-natural and afforestation condition, the morphological and physiological adaptability variations of two sympodial bamboo seedlings, namely, Oxytenanthera braunii (wine bamboo) and Dendrocalamopsis oldhami, were studied.We set up 5 nitrogen fertilization CO(NH2)2 levels, i.e. N0 (calculated by N content), N40, N80, N120, N160 kg/hm2 after 52.7 kg/hm2 Ca(H2PO4)2 and (K2SO4) K2O 56.3 kg/hm2 were applied into the soil. And 1 a later, we measured the morphological and photosynthesis characteristics. Results showed that wine bamboo had higher biomass and resource utilization efficiency compared with D. oldhami. And the optimal nitrogen fertilizer level for wine bamboo was about N120 while for D. oldhami was N80, so wine bamboo had higher utilization capacity. These two bamboos achieved their most optimized light utilization by elevating SLA, extending crown, increasing total leave areas and developing height. Meanwhile, the positive behavior was observed that the relative growth rate and root radius of wine bamboo and D. oldhami increased with the increase of nitrogen level. The nitrogen content of N160 was to high that it affected the optimal growth, but it was still better than N40 and the control treatment. Under the condition of medium nitrogen fertilizer supply (N80-N120), the physiological traits such as Pmax, LSP, LCP, Rd and φAQY were improved. The data of lower nitrogen supply like N40 treatment implied that the plasticity responses were not significant except for the root and φAQY.The higher biomass and SLA of wine bamboo, representing the capacity of absorbing carbon dioxide, implied that it could possess better adaptation and stronger propagation ability in the mid-high mountains of Southwest China after being introduced and afforested.The result of this study indicated that sympodial bamboo such as wine bamboo and D. oldhami should be planted on fertile soils where its habitat is managed to decrease the weeds growth, increase the root radius, branch length and total leaves areas so as to extend the crown to elevate photosynthesis and propagation rate.